Evaluasi karkas berdasarkan umur dan bobot badan ternak sapi di Kabupaten Manokwari: Carcass evaluation based on age and body weight of cattle in Manokwari District - Latuheru, Silvia D.; Monim, Hanike; Wajo, Muhammad Jen (Fakultas Peternakan Universitas Papua, 2024)
Abstract The aim of the research was to study the quality of livestock production in relation to carcass quality and body weight. The research was conducted descriptively using exploratory techniques on cattle and their products (carcasses). Research for 1 (one) month at the cattle slaughtering location in Manokwari district, namely the first slaughtering location is Transito Wosi, the second slaughtering location is Rendani and the third location is Wosi Market. Samples were obtained randomly by selecting 86 male cattle which were slaughtered with the following criteria: Age 1-2 years, Age 2-3 years, Age 3-4 years, Age 4-5 years and Age > 5 years. The results of this study indicate that the percentage of cattle slaughtered is based on age, namely 2-3 years of 67.44%, 3-4 years of 43.99%, while the highest carcass weight is in the 3-4 year age category of 162.89 ± 77. 32 kg, and the longest carcass length in the 4-5 year old cattle category was 122.40 ± 11.80 cm. Slaughter weight has a close relationship (94.72%) with carcass weight, carcass percentage and carcass length. Differences in age category had no effect on carcass weight, carcass length and carcass percentage. Body weight is strongly influenced by body length and chest circumference. It is necessary to carry out further research with observations starting from livestock rearing, feed given, livestock handling before to after slaughter, carcass quality (thickness of fat, area of rib eye veins). Keywords: Beef cattle; Carcass; Morphometric Abstrak Penelitian bertujuan mempelajari mutu produksi ternak dengan hubungannya dengan kualitas karkas serta berat badan. Penelitian dilakukan secara deskriptif dengan teknik eksplorasi pada ternak sapi dan produknya (karkas). Penelitian selama 1 (satu) bulan pada lokasi pemotongan ternak sapi kabupaten manokwari yaitu lokasi pemotongan I adalah Transito Wosi, lokasi pemotongan II adalah Rendani dan lokasi III adalah Pasar Wosi. Sampel diperoleh secara acak dengan memilih 86 ekor ternak jantan yang disembelih dengan kriteria: Umur 1-2 tahun, Umur 2-3 tahun, Umur 3-4 tahun, Umur 4-5 tahun dan Umur > 5 tahun. Hasil penelitian ini menujukan bahwa Bahwa presentase sapi yang dipotong berdasarakan umur yakni 2 -3 tahun sebesar 67,44%, 3-4 tahun 43,99%, sedangkan bobot karkas tertinggi pada kategori umur 3-4 tahun sebesar 162,89±77,32 kg, serta panjang karkas terpanjang pada kategori umur sapi 4-5 tahun sebesar 122,40±11,80 cm. Bobot potong memiliki hubungan yang erat (94,72 %) dengan bobot karkas, persentase karkas dan panjang karkas. Perbedaan kategori umur tidak berpengaruh terhadap bobot karkas, panjang karkas dan persentase karkas. Bobot badan sangat dipengaruhi oleh panjang badan dan lingkar dada. Perlu dilakukan penelitian lebih lanjut dengan pengamatan yang dimulai dari pemeliharaan ternak, pakan yang diberikan, penanganan ternak sebelum sampai sesudah ternak dipotong, kualitas karkas (tebal lemak, luas urat daging mata rusuk). Kata kunci: Karkas; Morfometrik; Sapi potong